Congenital vaginal obstruction in a female with Cornelia de Lange syndrome: A case report - Shen, Yiding; Zhao, Dongyan; Sun, Long; Yang, Xiuzhen; Yan, Xiang (Frontiers in Endocrinology, 2022)
Cornelia de Lange syndrome (CdLS) is a rare genetic disease involving multiorgan systems that varies in clinical manifestations. Female genital abnormalities in patients with CdLS are rarely reported, and current guidelines for CdLS contain little information related to female genital abnormalities. We report a case of classic CdLS with an NIPBL gene pathogenic variant in a 4.5-year-old girl who experienced recurrent urinary tract infections (UTIs) with vesical tenesmus. Urogenital physical and imaging examinations revealed external vaginal orifice obstruction and bilateral vesicoureteral reflux (VUR). Vaginal diaphragm-like tissue resection and vaginal orifice plasty were performed on this patient. The symptoms of urination disorders and recurrent UTIs, as well as VUR grading, improved after relieving the vaginal obstruction during the operation. For female CdLS patients, especially those with VUR, it is necessary to check for genital abnormalities and perform timely treatment, which is of great significance in improving urination disorder symptoms, reducing resistance during voiding, decreasing the occurrence of secondary VUR, and controlling recurrent UTIs.